Anxiety Management Penderita Covid-19: Studi Fenomenologis - Rahmadini, Amalia Fajar; Malik, Amaliah Fadilah (Syntax Corporation, 2026)
Covid-19 disease has led to various psychological problems faced by sufferers. Previous studies have found anxiety as one of the most common symptoms in sufferers. This study aims to determine the description of the experience of anxiety and anxiety management experienced by Covid-19 sufferers who have been declared cured. A total of 4 participants were interviewed in depth. Data analysis in this study used the phenomenological method to obtain essential experiences in all participants. Participants after being diagnosed with Covid-19 expressed anxiety and worry during the self-isolation or treatment process. The results of the study obtained 6 themes regarding the experience of anxiety, including: (1) External conditions or threats, (2) Cognitive and affective responses, (3) Physical responses, (4) Social responses, (5) Coping strategies, and (6) Aftereffects.